"Let them fly”: experiences of sending parents in international high school exchange programs - Falcon Campos, Cruz Joel Isaac (Kansas State University, 2018)
Every year more than 100,000 high school students around the world embark on a journey to study abroad for a few weeks up to a full year (CSEIT, n.d.). Most studies of international exchange programs address the university level, while very few researchers have examined high school study abroad. Of those who have, the focus has been almost exclusively on individual exchange students. For example, researchers have identified that some of the benefits for exchange students include developing a broader global perspective (Gu, Schweisfurth, & Day, 2010), increasing their intercultural competence, maturity, and sensitivity (Shiri, 2015), an increase in their personal development and growth (Geeraert & Demoulin, 2013), and increases in self-confidence (Hadis, 2005). While exchange students are in a unique position of being members of two families, the literature focusing on sending parents is currently nonexistent. The current applied qualitative study focused on investigating and giving voice to 26 sending parents’ living experiences. The participants in this study were in four participating countries – Denmark, Hungary, Norway, and Turkey. Using the lenses of family systems theory, these individual cases generated general patterns and common themes through collaborative, inductive, cross-case analysis. The results suggested that the experience of sending parents offers them some benefits at the micro and the macro levels (for themselves, their families, and for the world community). The analysis also revealed several challenges they faced and the coping strategies they utilized before, during, and after their teenagers studied abroad. This project begins to build a body of knowledge about the sending parents’ experiences, needs and strategies that can help guide the development of evidence-informed best practices as well as open a body of knowledge that can be essential to preparedness and understanding of exchange programs, to family professionals, host families, sending families, international students, our local communities and schools, and to assist them in their collaboration with each other to make these important, life-changing, world-changing experiences even better.
Keywords: International; Parenting; Qualitative; Exchange Students; Family